İLKÖĞRETİM 6, 7 VE 8. SINIF TÜRKÇE DERS KİTAPLARINDAKİ DİLBİLGİSİ TERİMLERİ ÜZERİNE BİR İNCELEME - DEMİRKOL, SELMİ (Fırat Üniveristesi, 2007)
Dil, genel dilbilimin kurucusu olarak sayılan Saussure'ün de ifade ettigi sekliyle bildirisimi saglayan göstergeler dizgesidir. nsanların yasamını düzenleyen, onları bir arada tutan ve bireyleri milletlesme çizgisine tasıyan en önemli unsur olan dil, varlıgı ve dıs dünyayı algılamamızı saglayan en önemli araçtır. Bu yüzden alıcı dil özelligi tasıyan ilkögretim çagındaki ögrencilere mükemmel bir ana dili egitimi verilmelidir. Dil/ana dili egitiminin kaliteli bir sekilde verilmesi ve o dilin bilinçli bir sekilde kullanılması, o dildeki dilbilgisi kurallarına vakıf olmakla mümkündür. Bu da ancak bilinçli dil egitiminin verildigi ilkögretim yıllarında okutulacak olan ders kitaplarında ortak gramer terimlerinin kullanılmasıyla olur. Çünkü dogru bir dilbilgisi ögretimi, dilbilgisi ögretiminde kullanılan terimlerin tutarlı ve ortak olmasına baglıdır.

Language is system of signs supplying a communication, as Saussure?s express that is founder of general linguistics. Language which supply our perceive existence and out world is the most important means arraying of peoples life, them gathering and individuals carrying national line. Therefore, excellent a language education is must given to students of primary education level. Of good quality language education has been given and of this language has been consciously used is possible with to know grammatical rules of language. But this can be with put into place of common grammar terms to materials being will been read of conscious language education given. Because true a grammatical education dependent on common be of used terms in grammatical education. Reasons not being consistent and common in the education and instruction process will to occur concept confusion. Therefore in this investigation in education and instruction process as using the most effect material grammatical terms and these interest differences in the lesson books have been made. This study has been made to determine grammar terms in the Turkish lesson books of 6, 7 and 8 class.
Investigation on grammar terms in the books of Turkish lesson of 6, 7 and 8th class of primary education
Keywords: Türk Dili ve Edebiyatı